The effect of interstate travel on sleep patterns of elite Australian Rules footballers - Richmond, L.; Dawson, B.; Hillman, D. R.; Eastwood, P. R. (Journal of Science and Medicine in Sport, 2004)
The purpose of the current study was to examine the effect of interstate air travel on the quality and quantity of sleep in elite Australian Rules football players. Ten elite male athletes, who were members of a Western Australian-based Australian Football League (AFL) team, participated in the study. Sleep pattern was assessed by measuring sleep duration (SLD), sleep efficiency (SE), number of wakings (NW) and total wake time after sleep onset (WT) using a wrist-worn actigraph. Subjective sleep quality (SQ) was assessed using a scale of sleep rating. Throughout the 2002 AFL season, measurements were obtained on the night before (N1), the night of (N2) and the night after (N3) home and away games. Baseline measurements were obtained from five consecutive non-game nights. Compared to baseline, SLD on N1 was increased when home and away (by 51 and 105 mins respectively, p<0.05), while all other measures of sleep pattern were unchanged. On N2, SLD was decreased to a similar degree whether home or away (by 68 and 64 mins respectively, p<0.05), while all other measures of sleep pattern were unchanged. By N3 all measures of sleep pattern had returned to baseline values. Relative to baseline, perception of SQ was worst on N2 of a home game. This study has shown that interstate travel by elite AFL players has no adverse effects on sleep pattern on the night before a game.